Approaches to active tourism in the Urals and in Perm Krai - Ziryanov, Aleksander I.; Korolev, Andriej Y.; Mishlavtceva, Swietlana E.; Safarian, Azat A. (Turyzm/Tourism, 2016)
Located in the south of Ural, Perm Krai, apart from mineral resources and well-developed industry, can boast vast areas that lend themselves to active and qualified tourism, with the quality of an amateur sport. The development of these forms of tourism often requires large expenditure needed for adjusting the space to various types of activity. It also requires a correlation between a given character of the space and the preferred form of tourism, which often leads to environmental conflicts between the development of tourism and nature protection. The article presents the most important elements of the tourism potential in Perm Krai, as well as the sports tourism development perspectives in the context of real and potential environmental conflicts.